Smart Materials, Adaptive Structures and Intelligent Systems, Volume 2 2008
DOI: 10.1115/smasis2008-592
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Guided Wave Imaging Techniques in Structural Health Monitoring

Abstract: Ultrasonic guided waves, due to theirs capability of interrogating a large structure from a single sensor position, has been proven as a promising tool for structural health monitoring (SHM). In this paper, we present two imaging approaches of utilizing guided wave leave-in-place sensors for early detection of defects in plate-like structures as well as for monitoring the defect growth. The first approach is based on a guided wave tomographic technique, in which the region surrounded by a sparse sensor array i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…3 Guided wave-based sparse sensor damage detection techniques have been explored by numerous authors. [6][7][8][9][10][11] Among those, Kessler et al 12 presented a technique capable of detecting defects in quasi-isotropic composite materials by recording the time evolution of the wavefield at few points using only PZT sensors. More recently, Yu et al 13 showed that in metallic isotropic materials, sparse sensor guided wave techniques can be used to determine damage location and, in some cases, damage size.…”
Section: Introductionmentioning
confidence: 99%
“…3 Guided wave-based sparse sensor damage detection techniques have been explored by numerous authors. [6][7][8][9][10][11] Among those, Kessler et al 12 presented a technique capable of detecting defects in quasi-isotropic composite materials by recording the time evolution of the wavefield at few points using only PZT sensors. More recently, Yu et al 13 showed that in metallic isotropic materials, sparse sensor guided wave techniques can be used to determine damage location and, in some cases, damage size.…”
Section: Introductionmentioning
confidence: 99%
“…Through the similar processes for all angles, the virtual scanning can be achieved without any physical manipulation of the array. Since constructive interference for the damage scattered signals is actually realized during beamforming, the signal-to-noise (SNR) of diagnostic signals and inspection distance can be largely improved [35]. An image of the scanned area is finally generated by directly mapping all the synthetic signals with the known velocity.…”
Section: Lamb Wave Methodsmentioning
confidence: 99%
“…In aeronautic structures, composite materials are increasingly utilized to decrease weight for payload and radius purposes. The percentages by weight of composites in USA fighters rise from 2% in F-15E to 35.2% in F-35/CV. The overall structure of Eurofighter Typhoon is composed of 40% carbon-fiber composite materials.…”
Section: Composite Materialsmentioning
confidence: 99%
“…In addition, for the experimental cases, a very dense sensor network is required to obtain reliable results. 59,61 This is not very attractive option for application to real structures due to the additional weight of the sensors and wires and the extra acquisition time.…”
Section: Tomography Approachmentioning
confidence: 99%